Cost-effectiveness of implementing HIV and HIV/syphilis dual testing among key populations in Viet Nam: a modelling analysis. Issue 8 (11th August 2022) - Coomes, David; Green, Dylan; Barnabas, Ruanne; Sharma, Monisha; Barr-DiChiara, Magdalena; Jamil, Muhammad S; Baggaley, R; Owiredu, Morkor Newman; Macdonald, Virginia; Nguyen, Van Thi Thuy; Vo, Son Hai; Taylor, Melanie; et al.
Abstract : Objectives: Key populations, including sex workers, men who have sex with men, and people who inject drugs, have a high risk of HIV and sexually transmitted infections. We assessed the health and economic impacts of different HIV and syphilis testing strategies among three key populations in Viet Nam using a dual HIV/syphilis rapid diagnostic test (RDT). Setting: We used the spectrum AIDS impact model to simulate the HIV epidemic in Viet Nam and evaluated five testing scenarios among key populations. We used a 15-year time horizon and a provider perspective for costs. Participants: We simulate the entire population of Viet Nam in the model. Interventions: We modelled five testing scenarios among key populations: (1) annual testing with an HIV RDT, (2) annual testing with a dual RDT, (3) biannual testing using dual RDT and HIV RDT, (4) biannual testing using HIV RDT and (5) biannual testing using dual RDT. Primary and secondary outcome measures: The primary outcome is incremental cost-effectiveness ratios. Secondary outcomes include HIV and syphilis cases. Results: Annual testing using a dual HIV/syphilis RDT was cost-effective (US$10 per disability-adjusted life year (DALY)) and averted 3206 HIV cases and treated 27 727 syphilis cases compared with baseline over 15 years. Biannual testing using one dual test and one HIV RDT (US$1166 per DALY), or two dual tests (US$5672 per DALY) both averted an additional 875 HIV cases, although only the former scenario was cost-effective. Annual or biannual HIV testing using HIV RDTs and separate syphilis tests were more costly and less effective than using one or two dual RDTs. Conclusions: Annual HIV and syphilis testing using dual RDT among key populations is cost-effective in Vietnam and similar settings to reach global reduction goals for HIV and syphilis.